Bonnie C. Wade: Thinking Musically: Experiencing Music, Expressing Culture; Adelaida Reyes: Music in America.: Oxford University Press, edice The Global Music Series, New York – Oxford 2004; Oxford University Press, edice The Global Music Series, New York – Oxford 2005, 123 s. + CD (33 ukázek) - Jurková, Zuzana (Lidé města, 2006)
A review of two books by Bonnie C. Wade and Adelaida Reyes.